Polyharmonic Kirchhoff problems involving exponential non-linearity of Choquard type with singular weights. (July 2020) - Arora, R.; Giacomoni, J.; Mukherjee, T.; Sreenadh, K.
Abstract: In this work, we study the higher order Kirchhoff type Choquard equation ( K C ) involving a critical exponential non-linearity and singular weights. We prove the existence of solution to ( K C ) using Mountain pass Lemma in light of Moser–Trudinger and singular Adams–Moser inequalities. In the second part of the paper, using the Nehari manifold technique and minimization over its suitable subsets, we prove the existence of at least two solutions to the Kirchhoff type Choquard equation ( P λ, M ) involving convex–concave type non-linearity.